Amino acid transporters in breast cancer: promising prognostic markers and emerging targets across molecular subtypes - El Ansari, Rokaya (2020)
Background: To maintain the necessary energy and cellular building blocks, tumour cells selectively upregulate expression of cell-surface nutrienttransporters. One of the most prominent are amino acid transporters, which catalyse the uptake of vital amino acids, particularly glutamine. Glutamine promotes cell growth by supporting bioenergetic and biosynthetic metabolism, maintaining redox balance and activating the mTORC1 signalling pathway, which supports protein translation and prevents apoptosis in cancer cells. These metabolic alterations are mediated by mutations in oncogenes and/or tumour suppressors that result in sustained cancer cell growth and proliferation. Cellular interaction with a tumour microenvironment, at the metabolic level, can also promote cancer aggressiveness and metastasis. Breast cancer (BC) is a heterogeneous disease with various subtypes that differ in terms of biology and clinical behaviour. There is growing evidence that differences in amino acid metabolism exist between BC molecular subtypes. However, the expression of amino acid transporters and the subsequent prognostic implications in BC remain elusive, especially with regard to the BC molecular subtypes. It was therefore hypothesised that amino acid transporters involved in the glutamine pathway are overexpressed in BC and they have prognostic implications that vary between BC molecular subtypes. This study aimed to determine the prognostic significance of the eminent amino acid transporters and their downstream signal in different BC molecular subtypes and to investigate the usability of the key amino acid transporters as potential targets for therapeutic interventions in BC. Furthermore, this study sought to find whether upregulation of amino acid uptake in BC participates in shaping the tumour microenvironment through attracting specific immune cell subtypes, including the subsequent impact on patient outcome.